Kane Method Based Dynamics Modeling and Control Study for Space Manipulator Capturing a Space Target. (20th July 2016) - Han, Yanhua
Abstract : Dynamics modeling and control problem of a two-link manipulator mounted on a spacecraft (so-called carrier) freely flying around a space target on earth's circular orbit is studied in the paper. The influence of the carrier's relative movement on its manipulator is considered in dynamics modeling; nevertheless, that of the manipulator on its carrier is neglected with the assumption that the mass and inertia moment of the manipulator is far less than that of the carrier. Meanwhile, we suppose that the attitude control system of the carrier guarantees its side on which the manipulator is mounted points accurately always the space target during approaching operation. The ideal constraint forces can be out of consideration in dynamics modeling as Kane method is used. The path functions of the manipulator's end-effector approaching the space target as well as the manipulator's joints control torque functions are programmed to meet the soft touch requirement that the end-effector's relative velocity to the space target is zero at touch moment. Numerical simulation validation is conducted finally.